Improving the Ability of Writing Story with the Inquiry Method of Students in Class X SMA Negeri 1 Botomuzoi 2020/2021 Academic Year - Agusmawati Mendrofa (Indonesian Journal of Education and Mathematical Science, 2022)
Writing is a process in order to convey an idea, a short message, and an opinion to the reader using symbols or language symbols. The short story is the presentation of a separate situation or a group of circumstances that gives a single message to the reader's soul. Writing a short story is an activity to arrange words into a written work that can give a single message to the soul of the reader. The purpose of this study was to improve students' ability in writing short stories using the inquiry method. This research uses Classroom Action Research (CAR) with implementation procedures consisting of planning, action, observation, and reflection. This research was conducted at SMA Negeri 1 Botomuzoi with 18 subjects, 10 boys and 8 girls. This activity was carried out in two cycles using data collection techniques, observation sheets, and assessment sheets. Data were analyzed in three stages, namely data reduction, data exposure, and conclusions. From the results of this study, it is evident that there is an increase in students' ability in writing short stories using the inquiry method. This is evident in the research findings of each cycle, namely cycle I with the average value achieved by students of 65.84. Whereas in cycle II there was an increase with the highest result with an average value of 86.38. Based on the results of this study, it can be concluded that the inquiry method can improve students' abilities in writing short stories and students are more active in the learning process. Researchers suggest the following: for teachers to familiarize students with writing short stories using the inquiry method, for future researchers, in order to find factors that influence the inquiry method in short story writing material.